The Command to Rule over the Creation (Gen 1:26–28) in the Ecological Hermeneutics of the Bible - Twardziłowski, Tomasz (Collectanea Theologica, 2021)
In the discussions on the possible religious background of the current ecological crisis, the biblical text of Genesis 1:26–28 is the passage most often quoted by all sides of the debate. While for some it is an incentive to unlimited exploitation, and the resultant degradation of the natural environment, for others it carries a positive ecological message and a call for responsible care of the created world. Due to this ambiguity in interpretations, this article attempts to resolve whether the biblical text itself is problematic, and requires correction, or whether it is ecologically adequate, and it is the interpretations that have been thus far insufficient. Each of the three main currents of the ecological hermeneutics of the Bible (apologetic, radical, and neo-orthodox) offers its own specific answer to this question.